A Metadata Driven Approach to Educational Adaptive Hypermedia - Connor, Niamh (Trinity College Dublin. Department of Computer Science, 1999)
The objective of this dissertation is to develop a teaching tool which extends the benefits of Web learning by providing increased flexibility for both students and administrators. The dissertation will investigate the technical and pedagogic requirements for courseware customisation to support constructivist based learning, design and develop a demonstrator capable of runtime customisation of WWW courseware based on individual student profiles and evaluate the complexity in supporting and administering such systems.
Keywords: Computer Science